Influence of control mechanism on the flow field of duct at Mach 1.2 for area ratio 2.56 - Khan, Sher Afghan; Aabid, Abdul; Chaudhary, Zakir Ilahi (Blue Eyes Intelligence Engineering & Sciences, 2019)
In this paper, the outcome of the experimental investigation and the flow field development in the duct at a supersonic Mach number of 1.2 is presented. The experiments were conducted at various NPR which covers the condition of correct expansion and under expansion. A Convergent-divergent (C-D) nozzle which is connected with the suddenly expanded duct of the diameter of 16 mm of area ratio 2.56. The recirculation zone is controlled by using the microjets of 1 mm of orifice diameter which is placed at 90 degrees interval at 6.5 mm from the central axis of the main jet. The L/D of the duct was used in the investigation was from 1 to 10, and the NPR at which the experiments were conducted considered are in the range from 3, 5, 7, 9 and 11